ANALISIS RESPON SPONTAN BENIH BENING LOBSTER JENIS PASIR (Panulirus homarus) TERHADAP WARNA CAHAYA BAWAH AIR YANG BERBEDA PADA UJI SKALA LABORATORIUM - Savilla Okta Wahyudi (Universitas Mataram, 2026)
Sand lobster (Panulirus homarus) is one of the high-value fishery commodities. The capture of peurulus generally uses passive fishing gear known as “pocong.” The use of underwater light as an aid in capture has the potential to increase effectiveness in attracting peurulus. This study aims to analyze the spontaneous phototactic response of peurulus to variations in underwater light color. Phototactic response is manifested as the position of the zone at the end of the light exposure period. The zone is divided into five sections, with the underwater LED light placed in the fifth zone. The study was conducted at the Aquaculture Laboratory of Hang Tuah University, using a completely randomized design (CRD) with three treatments of underwater LED light colors: white, red, and purple, each with a power of 3 watts, and each treatment was repeated 20 times. The independent variable was light color, and the dependent variable was the phototaxis response measured based on the zoning of the larvae's position at the end of light exposure. The results of the Mann-Whitney test showed a significant difference between white and purple light (p<0.05), while there was no significant difference between white-red and red-purple light. Peurulus showed the highest positive phototaxis response trend under white light (average zone 2.8), followed by red (average zone 2.7) and the lowest under purple (zone 2.1). This response is thought to be influenced by differences in wavelength and light intensity produced by each color. Underwater light color affects the phototaxis response of sand lobster larvae, white light being more effective at attracting attention compared to red and purple.